Upaya Peningkatan Pengetahuan dan Sikap Siswa SMP dalam Pencegahan Penggunaan NAPZA - Sumbung, Heryanto; Martha, Evi (Jurnal Promosi Kesehatan Indonesia, 2020)
Background: Ransiki is a district in South Manokwari Regency which was a new division in West Papua Province. Junior high school students in Ransiki are at risk of drug use. An effort should be made to improve the knowledge and attitude of junior high school students as a form of prevention of drug use. This study aimed to improve knowledge and attitude for the prevention of drug use in junior high school students in Ransiki using the training module "Pengenalan Bahaya NAPZA bagi Kesehatan".Method: This was a Pre Experimental study using the one group pre-test and post-test design. The study samples were 60 students. Samples were determined by purposive sampling. The intervention was conducted by providing module training for five meetings. The pre-test and post-test of students were analyzed using the Dependent T-test.Results: The results showed there was a significant relationship between the mean score of students’ knowledge before the intervention (39.44) and after the intervention (77.77) (p-value = 0.0001). There was a significant relationship between the mean score of students’ attitudes before the intervention (73.40) and after the intervention (82.40) (p-value = 0.0001). The training module "Pengenalan Bahaya NAPZA bagi Kesehatan" can be used to improve students' knowledge and attitude to prevent drug use in junior high school students of South Manokwari Regency